Principle and propensity: experience and religion in the nineteenth-century British and American Bildungsroman - Bennett, Kelsey L. (University of South Carolina Press, 2014)
John Wesley's formative "spiritual empiricism" -- The paradox of experience in Jonathan Edwards -- Pietism and the "free movement" of self-cultivation: synthesis and transformation in Wilhelm Meister's apprenticeship -- To enjoy my own faculties as well as to cultivate those of other people: the affective bildung of Jane Eyre -- "Faith in the immanence of spirit": Arminian self-formation in David Copperfield -- Pierre, or Melville's anarchic Calvinist bildungsroman -- "An impulse more tender and more purely expectant": the ardent good faith of Isabel Archer